Investigation of the antibacterial activity of synthesized hydroxyapatite Sr-doped nanocomposite - Novesar Jamarun, Laila Nur Afriska, Diana Vanda Wellia, Arika Prasejati, Tri Yupi Amirullah, Wulandari, Nabiila Ayyu Trycahyani (Journal of Applied Pharmaceutical Science, 2024)
Hydroxyapatite is a mineral compound with a composition resembling the components found in human teeth and bones. Hydroxyapatite possesses osteoconductive, bioactive, and biocompatible characteristics. Nevertheless, hydroxyapatite has limitations, particularly its limited antibacterial activity. Therefore, this research uses the sol-gel method to synthesize and characterize strontium hydroxyapatite doped composites (HAp-Sr doped composites). The calcium precursor used in this research comes from the green mussel shells (Perna viridis); the main component is CaCO3, which will later be converted into CaO compounds. HAp Sr-doped composites were synthesized by varying the concentration of Sr metal (5%, 10%, and 20% w/w), which aimed to determine its good antibacterial ability. The X-ray fluorescence analysis reveals that green mussel shells contain 97.261% calcium oxide (CaO). The X-ray diffraction analysis reveals that the pattern observed at an angle of 2θ corresponds to the hydroxyapatite standard from ICDD (No.96-101-1243), which possesses a hexagonal structure. The Fourier transform infrared spectroscopy spectra reveal the presence of PO43− groups in the sample at wave numbers 528 cm−1, 604 cm−1, 945 cm−1, and 1,018 cm−1. The antibacterial activity of the HAp-Sr doped composite was evaluated against Staphylococcus aureus and Escherichia coli bacteria. The results indicated that the 5% HAp-Sr doped composite exhibited antibacterial activity. Therefore, it can potentially be utilized in bone grafts and implants.
Keywords: Hydroxyapatite, strontium doped, green mussel shells, antibacterial activity